Indication of Disrupted Temporal Structure in the Case of Thought Blocks in Schizophrenia: The Role of the Metastable Balance - Elias Koutsoukos; Elias Angelopoulos (Behavioural Neurology)
This study is aimed at investigating probable disruption of the metastable balance relevant to a disruption of the mental processes observed in the neurophenomenal level. This disruption was found to occur under dense auditory verbal hallucinations (AVHs) which are accompanied by thought blocking (TB) phenomena. The entropy that quantifies the complexity of the spontaneous coupling has been used to describe the observed transitions. According to our findings, the high synchrony-derived entropy (SE) defines a metastable state, where formations of cortical areas are able to coordinate transiently under the demands of stimulus-oriented processes or other internal cognitive associations. It was also found that the disruption of the sensitive balance to the side of oversynergy (overconnectedness) rather than the side of independence (coincidental coupling) is relevant with functional fixations under the specific symptom of schizophrenia. An introduced measure relative to the persistence of coupling indicated that the overcoupled brain areas exhibit a kind of “stiffness” in processing incoherent phasic components. Our consideration enhances the understanding of the role the metastability plays in the interpretation of deeply subjective phenomena, such as AVHs and TBs that affect the normal information routing in the brain.